Is partial wrist denervation beneficial in chronic wrist pain? A systematic review. Issue 10 (October 2020) - Kadhum, Murtaza; Riley, Nicholas; Furniss, Dominic
Summary: Background: The prevalence of chronic wrist pain and subsequent functional decline is increasing. Diagnosis is challenging, with non-surgical treatment frequently failing. Recently, partial wrist denervation (PWD) has gained popularity as a procedure to alleviate chronic pain. Methods: A systematic review was performed in April 2019. Inclusion criteria involved clinical studies with a minimum of ten wrists, focusing on PROMs, objective measures of function and complications. Papers investigating complete or mixed denervation procedures were excluded. Results: Nine studies were included (292 wrists), all of which were observational in study design and limited in patient numbers, evaluation techniques and follow-up length. PWD appears to be associated with a reduction in pain, and functional improvement. Further surgery was required in 54 (24%) wrists at an average follow-up of 18 months. PWD was not found to complicate further surgery. Conclusion: PWD is associated with improvement in short-term pain relief and functional status, yet carries a high re-operation rate without contraindicating further salvage surgery. Further research is required to evaluate the benefits, duration of relief and long-term complications of PWD.